Gestión pedagógica en el aula: Clima social escolar, desde la percepción de estudiantes y profesores del Séptimo Año de Educación Básica de los centros educativos La Inmaculada¨ y Pasos del cantón Cuenca, provincia del Azuay, 2011-2012 - Guapisaca Juca, Vilma lorena (2013)
The work aims to conduct national research on "Managing classroom teaching: school social environment, from the perception of students and teachers of the seventh year of Basic Education central urban school" La Inmaculada and the rural school "Pasos", like elements of measurement and the description of the environment in which it develops the educational process. The sample was applied to 40 students and two teachers in the classroom. It is a non-experimental, exploratory, and descriptive research. The research methods applied are: descriptive, analytic-synthetic, inductive, deductive, and statistician. A survey was used with the application of the questionnaire (CES) Moos and Trickett which measures Educational Management, diagnose pedagogical skills, application of rules and regulations and classroom environment. During the development of the research was detected the difficulty level involvement and control, by which it was a proposal educational improvement. Meanwhile, for the scientific content and the theoretical framework I would like to invite you to review the present work that will allow you to pursue the subject.